THE FEATURES OF DEFENCE MECHANISMS OF ADOLESCENTS IN THE CONTEXT OF PARENTAL ATTITUDES - Невоєнна, Олена Анатоліївна; Зібарова, Юлія Володимирівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
The article deals with the problem of defence mechanisms connection with the types of adolescents parental attitudes. Mechanisms of psychological protection are acquired during life, and therefore the important role in their formation is played by the context of child`s growing and educating. Due to the results of the study, we can state that the parental attitude is a factor of development for a personal defence mechanisms. Most mechanisms of psychological protection are found at the type of «authoritarian hyper socialization» parental relationship namely «projection» «compensation» «avoidance» and «regression». «Symbiotic» style in the family is a prerequisite for the manifestation of such protective mechanisms as «projection» and «compensation», and the presence of «cooperation» may be the basis for the formation of «compensation».